PRINSIP DASAR ISLAM TENTANG MANUSIA - B, Mahirah (Inspiratif Pendidikan, 2018)
Human creation has become a central theme from age to age and never answered so far. Although it has a lot of analysis and understanding about the real man is and where it comes from, as well as the answers that have been put forward to solve this great problem, but until now there has been not completed. Discussing about human being is like entering a very deep valley, although it could be in it, but is unable to lift the mystery surrounding. In the Islamic view of the absolute event through several stages, such as, germ until the fifth stage is the stage of physical/material, while the sixth stage is the stage of non-physical/immaterial. Biologically, humans have the same dependence with the animals and plants, but humans as bearers of the trust on earth, then he was given a position as a servant and at the same caliph. Therefore man in al-Quran perspective should include the scope of which gives the value of a plenary, the world and the hereafter that perform individual life based on the commandments of God.